Халқ достонларида оила тизимига оид лексемалар - Нарматова, М (SCIENCE and SOCIETY, 2022)
This article talks about the role, meanings, etymology of lexemes related to the family system in historical and domestic life, and the levels of their use in folk epics.
Keywords: folk epics; family system; literary language; lexemes; dictionary; Arabic language; Turkic languages